Good continuum of HIV care in Belgium despite weaknesses in retention and linkage to care among migrants. Issue 1 (December 2015) - Van Beckhoven, D.; Florence, E.; Ruelle, J.; Deblonde, J.; Verhofstede, C.; Callens, S.; Vancutsem, E.; Lacor, P.; Demeester, R.; Goffard, J.-C.; Sasse, A.
Abstract Background The Belgian HIV epidemic is largely concentrated among men who have sex with men and Sub-Saharan Africans. We studied the continuum of HIV care of those diagnosed with HIV living in Belgium and its associated factors. Methods Data on new HIV diagnoses 2007–2010 and HIV-infected patients in care in 2010–2011 were analysed. Proportions were estimated for each sequential stage of the continuum of HIV care and factors associated with attrition at each stage were studied. Results Of all HIV diagnosed patients living in Belgium in 2011, an estimated 98.2 % were linked to HIV care, 90.8 % were retained in care, 83.3 % received antiretroviral therapy and 69.5 % had an undetectable viral load (<50 copies/ml). After adjustment for sex, age at diagnosis, nationality and mode of transmission, we found lower entry into care in non-Belgians and after preoperative HIV diagnoses; lower retention in non-Belgians and injecting drug users; higher retention in men who have sex with men and among those on ART. Younger patients had lower antiretroviral therapy uptake and less viral suppression; those with longer time from diagnosis had higher ART uptake and more viral suppression; Sub-Saharan Africans on ART had slightly less viral suppression. Conclusions The continuum of HIV care in Belgium presents low attrition rates over all stages. The undiagnosed HIV-infected population, although not precisely estimated, but probably close to 20 % based on available survey and surveillance results, could be the weakest stage of the continuum of HIV care. Its identification is a priority along with improving the HIV care continuum of migrants.